2012
DOI: 10.1589/jpts.24.687
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of an Underwater Exercise Program for Patients with Peripheral Arterial Disease

Abstract: Abstract. [Purpose] This study investigated the effect of a simple underwater training program on ambulatory functions of patients with peripheral vascular disease. [Subjects and Methods] Seven male patients participated in supervised underwater exercise training for twelve weeks to determine the effect of the program on their ambulatory capacity through comparison of their pre-and post-training values of their ambulatory indices, including toe pressure, maximum ambulatory distance, and ankle brachial index. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…We have also previously demonstrated that swim training has beneficial effects on body composition, BP, arterial stiffness, muscular strength, and cardiorespiratory health in postmenopausal women with stage 2 hypertension (76). Additionally, warm water immersion (~28 -30°C) has been shown to reduce pain (2,45), improve blood flow (2,10), and decrease joint loading and stress on the lower-extremity musculature (10,56). In fact, it has been suggested that water immersion alone improves blood flow and BP in patients with PAD (64) and water immersion heat therapy may improve exercise tolerance in patients with PAD (1).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…We have also previously demonstrated that swim training has beneficial effects on body composition, BP, arterial stiffness, muscular strength, and cardiorespiratory health in postmenopausal women with stage 2 hypertension (76). Additionally, warm water immersion (~28 -30°C) has been shown to reduce pain (2,45), improve blood flow (2,10), and decrease joint loading and stress on the lower-extremity musculature (10,56). In fact, it has been suggested that water immersion alone improves blood flow and BP in patients with PAD (64) and water immersion heat therapy may improve exercise tolerance in patients with PAD (1).…”
Section: Introductionmentioning
confidence: 94%
“…Participants in the AQ group participated in an aquatic walking exercise-training program for 12 wk, 4 days/ wk, for 60 min/day (Table 1), and this was adapted from previous literature for older individuals and patients with PAD (2,47). Sessions were conducted in waist-to-chest-deep water (28 -30°C) in a group setting (2). Participants were allowed to use flotation devices as needed for safety purposes.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Underwater treadmill gait training utilizes water buoyancy to run a gait training session with alleviated weight. The training method is similar to the on-ground weight support treadmill gait training 2 , 3 ) . Underwater treadmill training itself is a complete work-out, by which subjects can practice walking; therefore, it is one of the gait training methods that can be normally used 2 , 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The training method is similar to the on-ground weight support treadmill gait training 2 , 3 ) . Underwater treadmill training itself is a complete work-out, by which subjects can practice walking; therefore, it is one of the gait training methods that can be normally used 2 , 3 ) . Most studies of gait training were of on-ground techniques and few studies have focused on underwater treadmill training.…”
Section: Introductionmentioning
confidence: 99%